Analisis Pengaruh Minat Belajar Dan Motivasi Belajar Mahasiswa Fakultas Kedokteran Dan Kesehatan Di Universitas Imelda Medan - Ilzana, Teuku Muhammad; Adelaidey, Asyrafun Nisa (Lembaga Dongan Dosen, 2024)
This research aims to analyze the influence of learning interest and learning motivation on the academic achievement of medical and health faculty students at Imelda University, Medan. Using a quantitative approach, this research involved 100 medical and health faculty students as respondents taken using a purposive sampling method. The instrument used in this research is a questionnaire that measures interest and motivation to learn using a Likert scale. The collected data was analyzed using descriptive statistics and multiple linear regression. The research results show that interest in learning and motivation to learn significantly influence student academic achievement, with interest in learning having a regression coefficient of 0.45 and motivation to learn of 0.38. This research emphasizes the importance of developing interest and motivation to learn in supporting the academic achievement of medical and health students, so that educational institutions are advised to implement learning strategies that can improve these two aspects